Great writing 3 : From great paragraphs to great essays - Folse, Keith S.; Solomon, Elena Vestri; Clabeaux, David (Boston Cengage Learning, 2010)
The Great Writing series uses clear explanations and extensive practical activities to help students write great sentences, paragraphs, and essays. Each book contains a wide variety of writing models in carefully selected rhetorical styles that provide practice in working with the writing process to develop a final piece of writing. Great Essays takes a step-by-step approach that centers on the essential processes and organizational strategies of teaching students how to effectively transition from paragraphs to essays.
Keywords: Ngôn ngữ Anh